Entomopathogenic fungi for control of soil-borne life stages of false codling moth, Thaumatotibia leucotreta (Meyrick) (1912) (Lepidoptera: Tortricidae) - Coombes, Candice Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2013)
False codling moth (FCM), Thaumatotibia leucotreta is an extremely important pest of citrus in South Africa and with the shift away from the use of chemicals, alternate control options are needed. One avenue of control which has only recently been investigated against the soil-borne life stages of FCM is the use of entomopathogenic fungi (EPF). In 2009, 12 entomopathogenic fungal isolates collected from South African citrus orchards showed good control potential during laboratory conducted bioassays. The aim of this study was to further analyse the potential of these isolates through concentration-dose and exposure-time response bioassays. After initial re-screening, concentration-dose response and exposure-time response sandconidial bioassays, three isolates were identified as exhibiting the greatest control potential against FCM in soil, Metarhizium anisopliae var. anisopliae (G 11 3 L6 and FCM Ar 23 B3) and Beauveria bassiana (G Ar 17 B3). Percentage mycosis was found to be directly related to fungal concentration as well as the amount of time FCM 5th instar larvae were exposed to the fungal conidia. LC50 values for the three isolates were not greater than 1.92 x 10â ¶ conidia.mlâ »â‚‘ and at the LCâ‚…â‚€, FCM 5th instar larvae would need to be exposed to the fungus for a maximum of 13 days to ensure a high mortality level. These isolates along with two commercially available EPF products were subjected to field persistence trials whereby net bags filled with a mixture of autoclaved sand and formulated fungal product were buried in an Eastern Cape citrus orchard. The viability of each isolate was measured on a monthly basis for a period of six months. All isolates were capable of persisting in the soil for six months with the collected isolates persisting far better than the commercially used isolates. Two of the isolates, G 11 3 L6 and G Ar 17 B3, were subjected to small scale laboratory application trials. Two formulations were investigated at two concentrations. For each isolate, each formulation and each concentration, FCM 5th instar larvae were applied and allowed to burrow into the soil to pupate before fungal application or after fungal application. Contact between fungi and FCM host is essential as, in contrast to pre-larval treatments, percentage mortality in post-larval treatments was low for both formulations and both isolates. For isolate G Ar 17 B3, a conidial suspension applied as a spray at a concentration of 1 x 10â · conidia.mlâ »â‚‘ obtained the highest percentage mortality (80 %). For isolate G 11 3 L6 however, both formulations performed equally well at a high, 1 x10â · conidia.mlâ »â‚‘ concentration (conidial suspension: 60 %; granular: 65 %) The results obtained thus far are promising for the control of FCM in citrus, but if these EPFs are to successfully integrate into current FCM control practices more research, some of which is discussed, is essential
Keywords: Tortricidae; Lepidoptera; Cryptophlebia leucotreta; Insect pests -- Biological control -- South Africa -- Eastern Cape; Tortricidae -- Biological control -- South Africa -- Eastern Cape; Citrus -- Diseases and pests -- Biological control -- South Africa -- Eastern Cape; Entomopathogenic fungi; Fungi as biological pest control agents; Biological pest control agents